2020
DOI: 10.1099/jmm.0.001187
|View full text |Cite
|
Sign up to set email alerts
|

Point of care testing of Influenza A/B and RSV in an adult respiratory assessment unit is associated with improvement in isolation practices and reduction in hospital length of stay

Abstract: Introduction. Every winter seasonal influenza and other viral respiratory infections increase pressure on the health services and are associated with nosocomial infection and morbidity. Aim. To compare provision of point-of-care (POC) testing with laboratory-based testing for influenza and RSV detection on an adult respiratory assessment unit to assess the impact on isolation practices and length of stay (LOS). Methodology. Prospective interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…8,10 To our knowledge, very few studies have assessed the impact of rapid molecular testing on patient isolation for respiratory viruses. 14,28 However our study showed a positive impact on compliance with preventive measures by increasing single-room assignment in the downstream unit among patients with a viral infection that requires isolation. These measures are critical for Nineteen patients are missing due to an unknown length of stay; the length of stay for patients still hospitalized on D30 was set at 30 days.…”
Section: Discussionmentioning
confidence: 67%
“…8,10 To our knowledge, very few studies have assessed the impact of rapid molecular testing on patient isolation for respiratory viruses. 14,28 However our study showed a positive impact on compliance with preventive measures by increasing single-room assignment in the downstream unit among patients with a viral infection that requires isolation. These measures are critical for Nineteen patients are missing due to an unknown length of stay; the length of stay for patients still hospitalized on D30 was set at 30 days.…”
Section: Discussionmentioning
confidence: 67%
“…However, the high cost of hospital molecular platforms, the complexity of the equipment required, the need for trained professionals and the delay of 2–4 h to obtain the results with frequent unavailability on weekends and during the night impaired the use of conventional NAATs for respiratory viral infections such as influenza or SARS‐CoV‐2 diagnosis even in hospital settings. Finally, the implementation of point‐of‐care molecular testing for SARS‐CoV‐2 RNA could deliver benefits to patient care admitted to hospital with COVID‐19‐related respiratory illness in terms of more rapid confirmation of coronavirus infection, a shorter length of stay, more rapid isolation practices of patients tested positive, and shorter turnaround time, as previously shown for influenza as compared to laboratory testing 25 …”
Section: Discussionmentioning
confidence: 92%
“…Finally, the implementation of point-of-care molecular testing for SARS-CoV-2 RNA could deliver benefits to patient care admitted to hospital with COVID-19-related respiratory illness in terms of more rapid confirmation of coronavirus infection, a shorter length of stay, more rapid isolation practices of patients tested positive, and shorter turnaround time, as previously shown for influenza as compared to laboratory testing. 25 The limitations of our study include a relatively small sample size, inability to control for sampling variability, and lack of an additional comparator method to discern the discrepancies between VitaPCR™ and multiplex rRT-PCR results. Another possible limitation is the freezing of nasopharyngeal samples before their use with the VitaPCR™ platform.…”
Section: Discussionmentioning
confidence: 97%
“…COVID-19 patients may also be co-infected by other respiratory viruses, especially influenza, respiratory syncytial virus and adenovirus, which are the most common viral pathogens reported. However, the pathophysiology mechanism has not been well understood and data available from recent published studies are not enough to understand whether a viral co-infection affects the prognosis of COVID-19 patients [ 7 , 27 , 28 ]. Recently, Alosaimi et al in a study including 48 COVID-19 patients, reported that Influenza AH1N1 was the most common detected virus among the co-infecting pathogens, found in 64% of patients.…”
Section: Introductionmentioning
confidence: 99%